Combination of Radiological and Clinical Baseline Data for Outcome Prediction of Patients With an Acute Ischemic Stroke - Ramos, Lucas A.; Os, Hendrikus van; Hilbert, Adam; Olabarriaga, Silvia D.; Lugt, Aad van der; Roos, Yvo B. W. E. M.; Zwam, Wim H. van; Walderveen, Marianne A. A. van; Ernst, Marielle; Zwinderman, Aeiko H.; Strijkers, Gustav J.; Majoie, Charles B. L. M.; et al. (Frontiers in Neurology, 2022)
Background: Accurate prediction of clinical outcome is of utmost importance for choices regarding endovascular treatment (EVT) of acute stroke. Recent studies on prediction modeling for stroke focused mostly on clinical characteristics and radiological scores available at baseline. Radiological images are composed of millions of voxels, and a lot of information can be lost when representing this information by a single value. Therefore, in this study we aimed at developing prediction models that take into account the whole imaging data combined with clinical data available at baseline. Methods: We included 3279 patients from the MR CLEAN Registry; a prospective, observational, multicenter registry of ischemic stroke patients treated with EVT. We developed two approaches to combine the imaging data with the clinical data. The first approach was based on radiomics features, extracted from 70 atlas regions combined to the clinical data to train machine learning models. For the second approach, we trained 3D deep learning models using the whole images and the clinical data. We compared models trained with only the clinical data with models trained with the combination of clinical and image data. Finally, we explored feature importance plots for the best models and identified many known variables and image features/brain regions that were relevant in the model decision process. Results: From 3279 patients included, 1241 (37%) patients had a good functional outcome (mRS ≤ 2) and 1954 (60%) patients had good reperfusion (eTICI ≥2b). There was no significant improvement by combining the image data to the clinical data for mRS prediction (mean AUC of 0.81 vs 0.80) above using clinical data only, regardless of the approach used. Regarding predicting reperfusion,. there was a significant improvement when image and clinical features were combined (mean AUC of 0.54 vs 0.61), with the highest AUC obtained by the deep learning approach. Conclusions: The combination of radiomics and deep learning image features with clinical data significantly improved the prediction of good reperfusion. The visualization of prediction feature importance showed both known and novel clinical and imaging features with predictive value.